Discrete coordination nanochains based on photoluminescent dyes reveal intrachain exciton migration dynamics - Ryojun Toyoda; Naoya Fukui; Haru Taniguchi; Hiroki Uratani; Joe Komeda; Yuta Chiba; Hikaru Takaya; Hiroshi Nishihara; Ryota Sakamoto (Nature Communications, 2025)
Abstract Elucidating exciton migration in polymer chains has been one of the major research goals in photophysics for over half a century. While great efforts have been made to understand picosecond phenomena by ultrafast spectroscopy, ambiguous molecular conformations and/or random polymer sequences have hindered the construction of an ideal exciton migration model. Here we present the creation of unique end-capped coordination nanochains and quantitative description of intrachain exciton migration therein. The nanochain features unique molecular architectures in discrete polynuclear complexes, with a linear and rigid structure, the defined number of metal nuclei, and charge neutrality. These features allow well-defined arrangement of emissive dye moieties, making the nanochain a sound platform for studying exciton dynamics. Readily accessible absorption spectroscopy, and photoluminescence lifetime and quantum yield measurements allow the construction of continuous-time Markov chains model, thereby estimating non-trivial exciton migration across the metal center.